Governance under the shadow of the law: trading high value fine art - Shortland, Anja; Shortland, Andrew J. (Springer, 2019)
The market for paintings by well-known artists is booming despite widespread concern about art crime and difficulties in establishing provenance. Public law enforcement is imperfect, and court cases often are deemed problematic. So how is the thriving art market governed in practice? We analyze the protocols used by the top auction houses to identify and resolve problems of illicit supply—fakes, forgeries and items with defective legal titles—through the lens of institutional analysis. We uncover a polycentric private governance system in which different actors govern distinct but overlapping issue areas, motivated by profit, prestige, or the search for truth. When the financial stakes rise, opportunistic behavior undermines the credibility of private governance. We argue that as litigious, super-rich investors entered the art market, the interaction between public law and the traditional private governance system restricted the supply of “blue chip” art, driving the escalation of prices.
Keywords: Art market; Private enforcement of rights; Fraud; Theft